PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS VIDEO ANIMASI PADA MATERI MASA PRA-AKSARA DI INDONESIA PESERTA DIDIK KELAS X.1 SMA NEGERI 1 BANDAR LAMPUNG - Sri Ani, Ketut; Wisnu Kurniawan, Putut; Nandia F, Aurora (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This re$se$arch is motivate$d by the$ lack of use$ of le$arning me$dia, low inte$re$st in le$arning stude$nts, and le$arning me$dia that are$ ofte$n use$d are$ still in the$ form of powe$r points and printe$d books. This study aims to de$te$rmine$ the$ de$ve$lopme$nt, e$ligibility and re$sponse$ of stude$nts to animate$d vide$o le$arning me$dia in le$arning the$ history of Pre$-Ancie$nt Pe$riod mate$rial class X.1 SMA Ne$ge$ri 1 Bandar Lampung. The$ re$se$arch me$thod use$d is R&D (re$se$arch and de$ve$lopme$nt) and through the$ ADDIE$ de$ve$lopme$nt proce$dure$, and through the$ ADDIE$ de$ve$lopme$nt proce$dure$ which consists of analysis, de$sign, de$ve$lopme$nt, imple$me$ntation, and e$valuation. Product validation was comple$te$d by linguist validators who state$d that the$ animate$d vide$o le$arning me$dia for le$arning the$ history of the$ Pre$-Ancie$nt Pe$riod mate$rial de$ve$lope$d obtaine$d an asse$ssme$nt re$sult of 4.6 with the$ inte$rpre$tation crite$ria “ve$ry valid”, while$ the$ re$sults of the$ mate$rial e$xpe$rt validation state$d that the$ animate$d vide$o le$arning me$dia for le$arning the$ history of the$ Pre$-Ancie$nt Pe$riod mate$rial de$ve$lope$d obtaine$d an asse$ssme$nt re$sult of 4.5 with the$ inte$rpre$tation crite$ria “ve$ry valid”, the$n the$ re$sults of the$ me$dia e$xpe$rt validation state$d that the$ animate$d vide$o le$arning me$dia for le$arning the$ history of the$ Pre$-Ancie$nt Pe$riod mate$rial de$ve$lope$d obtaine$d an asse$ssme$nt re$sult of 4.2 with the$ inte$rpre$tation crite$ria “ve$ry valid”. While$ the$ re$sponse$ of stude$nts in the$ fie$ld trial obtaine$d an ave$rage$ score$ of 4.4 with the$ inte$rpre$tation crite$ria of “ve$ry practical”. The$ de$ve$lopme$nt of animate$d vide$o le$arning me$dia for le$arning the$ history of Pre$-Ancie$nt Pe$riod mate$rial for class X.1 SMA Ne$ge$ri 1 Bandar Lampung stude$nts using the$ re$se$arch and9de$ve$lopme$nt (R&D) re$se$arch me$thod, it can be$ conclude$d that the$ use$ of animate$d vide$o le$arning me$dia for le$arning the$ history of Pre$-Ancie$nt Pe$riod mate$rial is ve$ry valid and ve$ry practical to use$ as le$arning me$dia.